2002
DOI: 10.1099/0022-1317-51-5-399
|View full text |Cite
|
Sign up to set email alerts
|

Subtype distribution of Haemophilus influenzae isolates from North India

Abstract: A total of 120 Haemophilus influenzae isolates from blood, cerebrospinal fluid, sputum and throat swabs of patients and carriers in North India was characterised by biotyping, ribotyping and random amplification of polymorphic DNA (RAPD)-PCR. Of these, 77 isolates (64%) were serotype b; the other 43 (36%) were non-typable. Biotype I was the most predominant among the typable strains and biotype II among the non-typable strains. Ribotyping with restriction endonucleases HaeIII and EcoRI differentiated the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Restriction with EcoRI produced only three distinct ribotypes with fragment sizes ranging from 300 to 6000 bp (data not shown); ribotyping with EcoRI is known to be limited in its discriminatory ability among non-typable isolates (Sharma et al, 2002). Six isolates (C2408, C2561, C2562, C2687, C2692 and C2696) produced an identical ribotype pattern, distinct from all other strains.…”
Section: Screening and Detection Of Hypermutable H Influenzae Isolatesmentioning
confidence: 99%
“…Restriction with EcoRI produced only three distinct ribotypes with fragment sizes ranging from 300 to 6000 bp (data not shown); ribotyping with EcoRI is known to be limited in its discriminatory ability among non-typable isolates (Sharma et al, 2002). Six isolates (C2408, C2561, C2562, C2687, C2692 and C2696) produced an identical ribotype pattern, distinct from all other strains.…”
Section: Screening and Detection Of Hypermutable H Influenzae Isolatesmentioning
confidence: 99%
“…An important finding of our study is that isolates from blood, CSF and sputum samples of patients showed complete agreement in their profiles produced by molecular approaches (Sharma et al, 2002) and OMP analysis. In the OMP analysis, the same three isolates from blood that presented ribotype A with EcoRI and RAPD type a with primers AP1 and AP2 in our previous study showed OMP subtype 6, while the strain of ribotype D and RAPD type d showed OMP subtype 8.…”
Section: Discussionmentioning
confidence: 74%
“…A total of 305 CSF samples and 41 blood samples from infants, throat swabs of 63 healthy children and adults and sputum samples from 25 adult patients were screened. Details of the samples and strains obtained were provided previously (Sharma et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations